Efektivitas Komunikasi Dakwah Digital Melalui Media TikTok Dalam Meningkatkan Pengamalan Agama Masyarakat Muslim Di Kelurahan Tanjung Mulia Medan Deli - Rusydi Aulia Siregar; Muktarruddin Muktarruddin (Jurnal Khabar: Komunikasi dan Penyiaran Islam, 2025)
This study aims to analyze the effectiveness of digital preaching (dakwah) using TikTok in enhancing religious practices among Muslim communities in Tanjung Mulia Medan Deli. A descriptive-correlational quantitative approach was employed, with data collected from 350 purposively sampled participants through structured questionnaires. Statistical analysis using Spearman’s correlation and linear regression revealed a significant positive relationship between digital dakwah access intensity and religious practice levels (? = 0.482; p < 0.001), contributing 23.2% of the variance (R² = 0.232). Key supporting factors included visual content quality (62.3%), stable internet infrastructure (78%), and collaborations between preachers and local influencers (34%), while major barriers were advertisement distractions (57.1%) and non-contextual material (28.6%). A unique "saturation effect" was identified, where excessive access (>3 hours/day) reduced religious practice scores. The study concludes that digital dakwah is partially effective, with optimal impact achieved through locally tailored content, robust infrastructure, and complementary community-based mentoring. These findings highlight the necessity of hybrid strategies integrating digital and conventional approaches to strengthen the internalization of religious values.